Knowledge on the Validity of the Hadith on Veil, the Obligation to Wear and Its Application in Social Life: A Case Study at UIN Alauddin Makassar - Hafid, Erwin; Mahmuddin, Mahmuddin; Mustafa Kamal, St Ibrah; M. Jakfar, Tarmizi; Syahabuddin, Syahabuddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This study seeks to assess the impact of students' degree of comprehension on the veracity of the hadith on veil, the law governing its wearing, and its application in their social lives. This study is a mixed-methods approach, using a case study as the methodology to get a full grasp of a specific legal matter in order to generate more understanding on the issue of veil. The data were collected through interviews, literature studies and surveys. The results revealed that the respondents' knowledge on the authenticity of the hadith was modest, while their comprehension of the legislation governing the wearing of the veil ranged between a lack of understanding and a sufficient understanding, and their application in daily life was quite high. In addition, it was discovered that there were reasons that influenced their persistent usage of the veil, given their strong commitment to doing so. These considerations include the external supports, for example the support of friends, families, and communities. Supposedly, if the acceptance of new behavior is founded on information, awareness, and a good attitude, this kind of behavior will be persistent. If, on the other hand, a behavior is not founded on knowledge and awareness, it will be easily left out. This case study also found that there were factors other than knowledge that influenced female students in social applications to wear the veil, namely support from family, friends and organizations.In the future efforts are needed so that knowledge about the authenticity and content of hadith law regarding the veil can be increased. So that a person can strike a balance between the spirit of religion and his knowledge of the law governing the text's authenticity (hadith) and Islamic law.